Autotransplantation of a mandibular third molar, using a customized reservoir - Kulkarni, Meera Uday (J Conserv Dent, 2020)
Autogenous transplantation is a fast and economical option when a suitable donor tooth is available for the replacement of nonsalvageable teeth. The preservation of the periodontal ligament (PDL) cells is considered to be critical for the success of a transplanted tooth. This article presents a successful case report of autotransplantation of a mandibular third molar using a novel technique to store the donor tooth extraorally during the surgical procedure and preserve the viability of PDL cells. One year of clinical and radiographic examination revealed no signs or symptoms suggestive of any pathology and the marginal adaptation of gingiva around the donor tooth appeared to be satisfactory. Inappropriate cases, this treatment approach may be considered as an alternative to conventional prosthetic rehabilitation or implant treatment.